Kinematical ‘Balances’* - Steinmann, Paul (Spatial and Material Forces in Nonlinear Continuum Mechanics, 2022)
This chapter applies the formats of the generic balances to the spatial and material tangent, cotangent, and measure maps to formulate what, for the sake of semantic unification, may be called kinematical ‘balances’.
CRIS-Team Scopus Importer:2022-04-15